Macrophage iron metabolism profile in proatherogenic conditions - Canonne-Hergaux, François (2015)
Atherosclerosis is currently considered as a chronic inflammatory disease, in which the subendothelial accumulation of macrophages and their differentiation in lipid−laden foam cells through the uptake of oxidized LDL (oxLDL) constitute key events in atherogenesis [1]. In such process, iron could constitute a modifiable factor [2] and characterization of the iron metabolism profile of the different macrophages phenotypes present in atherosclerotic lesions may provide insight on their potential protective or proatherogenic role. A new macrophage phenotype (Mox) driven by exposure to oxidized phospholipids was recently described in murine models of atherosclerosis [3]. Herein, we investigated the effect of oxLDL as well as proinflammatory stimuli on macrophage polarization and iron metabolism profile.